Answer:
(11 x - 20)/(x (x - 4)) = 11x-20/x^2-4x
Explanation:
Simplify the following:
6/(x - 4) + 5/x
Put each term in 6/(x - 4) + 5/x over the common denominator x (x - 4): 6/(x - 4) + 5/x = (6 x)/((x - 4) x) + (5 (x - 4))/((x - 4) x):
(6 x)/(x (x - 4)) + (5 (x - 4))/(x (x - 4))
(6 x)/((x - 4) x) + (5 (x - 4))/((x - 4) x) = (6 x + 5 (x - 4))/((x - 4) x):
(6 x + 5 (x - 4))/(x (x - 4))
5 (x - 4) = 5 x - 20:
(5 x - 20 + 6 x)/(x (x - 4))
Grouping like terms, 6 x + 5 x - 20 = (6 x + 5 x) - 20:
((6 x + 5 x) - 20)/(x (x - 4))
6 x + 5 x = 11 x:
Answer: (11 x - 20)/(x (x - 4))